2011
DOI: 10.1186/1752-1947-5-573
|View full text |Cite
|
Sign up to set email alerts
|

Severe brain atrophy after long-term survival seen in siblings with familial amyotrophic lateral sclerosis and a mutation in the optineurin gene: a case series

Abstract: IntroductionPrevious studies have shown widespread multisystem degeneration in patients with sporadic amyotrophic lateral sclerosis who develop a total locked-in state and survive under mechanical ventilation for a prolonged period of time. However, the disease progressions reported in these studies were several years after disease onset. There have been no reports of long-term follow-up with brain imaging of patients with familial amyotrophic lateral sclerosis at an advanced stage of the disease. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, a few patients required TIV over 24 months after the onset, such as our patient 3 with pTDP-43-ir NCI, and three patients reported in the existing literature, showing pTDP-43-ir NCI [ 11 ], basophilic inclusions [ 14 ], and a mutation in OPTN [ 28 ], respectively (Tables 1 and 3 ). These patients showed that patients who required TIV after more than 24 months from disease onset could not necessarily avoid progression to Stage V.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, a few patients required TIV over 24 months after the onset, such as our patient 3 with pTDP-43-ir NCI, and three patients reported in the existing literature, showing pTDP-43-ir NCI [ 11 ], basophilic inclusions [ 14 ], and a mutation in OPTN [ 28 ], respectively (Tables 1 and 3 ). These patients showed that patients who required TIV after more than 24 months from disease onset could not necessarily avoid progression to Stage V.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, patients with marked cerebral atrophy due to degeneration of the cerebral cortex and white matter have also been reported [ 11 , 17 , 20 ]. Neuroradiologically, a progressive cerebral atrophy has been shown in siblings with ALS who carried a mutation in the gene for optineurin ( OPTN ) [ 28 ]. However, the distribution and characteristics of the cerebral lesions are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many mutations in OPTN have been associated with disease, including some that are predicted to eliminate OPTN’s function [1] , [4] , [21] , [22] , [24] [28] , [30] , [35] . We chose to study the loss of function of Optn in the zebrafish with the sa0143 (L278X) mutant of optn (number sign in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent groups have implicated many different mutations in OPTN with this disease [2] [20] . Amyotrophic lateral sclerosis (ALS) is a progressive debilitating condition where the loss of spinal motor neurons leads to paralysis and death, and researchers have also found mutations in OPTN to be associated with various forms of this disease [21] [35] . More recently, mutations in OPTN have been implicated in the metabolic bone disorder Paget’s disease of bone [36] [38] .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in Optn have been implicated in development of human diseases such as glaucoma (Aung et al, 2003; Ueno et al, 2011), amyotrophic lateral sclerosis and Paget’s disease of the bone (Albagha et al, 2010). At this point, the role of Optn in immune cells is less well understood.…”
Section: Introductionmentioning
confidence: 99%